Early Complement and Fibrinolytic Activation in a Rat Model of Blast-Induced Multi-Organ Damage. (21st March 2019) - Yang, Zhangsheng; Aderemi, Olawale A; Zhao, Qingwei; Edsall, Peter R; Simovic, Milomir O; Lund, Brian J; Espinoza, Mark D; Woodson, Amber M; Li, Yansong; Cancio, Leopoldo C
Abstract: Objective: Blast injury is associated with multi-organ failure (MOF), causing significant morbidity and mortality in trauma patients. However, the pathogenesis of blast-induced MOF still remains obscure. In this study, we evaluate the pathophysiological changes related to blast-induced MOF in a clinically relevant rat model of blast injury. Methods: A moderate blast overpressure was applied to induce injury in anesthetized rats. Pathological changes were evaluated by H&E staining. Complement activation, plasminogen, and myeloperoxidase levels were analyzed by complement hemolytic assay (CH50) and/or ELISA in blood samples. Results: Analysis of lung, brain, and liver tissue at 24 hour after blast overpressure revealed severe injuries. The level of complement components C3 and C1q decreased in parallel with the reduction of CH50 level in injured animals at 1, 3, and 6 hours after blast. Consumption of plasminogen was also detected as early as 1 hour post-injury. Myeloperoxidase levels were elevated within 1 hour of blast injury. Conclusion: Our data reveal that blast injury triggers the complement and fibrinolytic systems, which likely contribute to blast-induced MOF. Conceivably, therapies that target these systems early may improve clinical outcomes in blast patients.